Cylindrical surfaces enable wavelength-selective extinction and sub-0.2 nm linewidth in 250 μm-gap silicon Fabry–Pérot cavities - Malak, Maurine (2013)
In this paper, we propose two different designs of micromachined Fabry-Pérot optical cavities, with first motivation of improving the quality factor (Q -factor) and in the same time allowing increased cavity length L. Our approach consists of providing a solution to the main loss mechanism in conventional FP cavities related to the expansion of the Gaussian light beam after multiple reflections inside the cavity. The first design is based on all-silicon cylindrical Bragg mirrors, which provide 1-D confinement of light. In addition to wavelength selectivity, the first design also demonstrates its potential for a new class of applications, including wavelength selective extinction through mode-selective excitation, where the fiber-to-cavity distance is used as the control parameter. The second design is based on cylindrical Bragg mirrors combined with a fiber rod lens to provide a complete solution for 2-D confinement of light. This approach outperforms the first design in terms of Q-factor, of nearly 9000 for around 250 μm-long cavity, which suggests its potential use for biochemical sensing and analysis as well as cavity enhancement applications requiring high Q.L values.